Gibberellic acid in the emergence and early development of star fruit seedlings - André Passigatto Ortelan; Arthur Cardozo Loriato; Marcus Vinicius Sandoval Paixão; Gabriel Fontana Donadia; Kassio Dalmonech Zanotti; Antônio Resende Fernandes (Universidade Estadual de Alagoas, 2023)
Star fruit (Averrhoa carambola L.) is an exotic fruit originating in Southeast Asia and has seeds with low germination. The objective was to evaluate the effect of gibberellin on the emergence and initial development of star fruit seedlings. The seeds were removed from the fruits and washed in running water, and placed in gibberellin solution 1,000 mg.L-1, 2,000 mg.L-1, 3,000 mg.L-1, 4,000 mg.L-1 and pure water as a control. for 30 minutes. Sowing was carried out by placing 1 seeds per 280 mL tube in a substrate containing ravine soil + tanned manure (3:1) in a randomized block experimental design. Thirty days after the emergence of the first seedling, the percentage of emergence, emergence speed index and mean emergence time were evaluated. Ninety days after the emergence of the first seedling, the seedling height, collar diameter, number of leaves, root length were evaluated; green and dry mass of the leaves, green and dry mass of the roots. The star fruit seed has a low percentage of germination, with low emergence rates, and the use of gibberellin was efficient to increase and accelerate emergence, showing a positive response to the variables plant height, number of leaves, stem diameter and length of the seed. source. The treatment with gibberellic acid had a positive effect on the emergence and development of star fruit seedlings, and on the mass production of leaves and roots, with the concentration of 1,000 mg.L-1 showing the best results.